Corporeality in distance teacher training: the pedagogy course in focus - Cecchetto, Jacqueline [UNESP]; Haas, Celia Maria (Univ Federal Sergipe, 2024)
This article focuses on the training of distance pedagogy teachers in a virtual public university in the State of Sao Paulo, Brazil, and their conceptions of corporality in initial training and teaching work. Distance training for teachers in Brazil is growing due to the demand of these workers to reach the university level and improve the quality of education. In distance education, the only time the student has the opportunity to put the knowledge into practice is during the supervised internship. Given that teachers are trained virtually for face-to-face teaching, the question that arises is: can virtual training cover the role of corporality in teaching, given that it is a profession of human interactions? Through qualitative, descriptive, and interpretive research, questionnaires were used to collect information from 21 participants, 15 men and 6 women. Through content analysis, the data were analyzed under 3 axes: Understanding of Corporality by the students; Importance of Corporality for Practice; Vocational Training and Constitution of Corporality. From the research it was possible to conclude that corporality constitutes a disposition that translates interaction technologies in the teaching and learning process and should receive more attention in teacher training that is carried out in distance education.
Keywords: Corporality; Distance education; Teacher training; Training devices; Pedagogy